Pengaruh Peer Group Education Terhadap Kesadaran Diri dan Kemampuan Personal Hygiene Saat Menstruasi pada Remaja di Pondok Putri Sabilul Hasan Probolinggo - Defi Sela Gunawan; Nafolion Nur Rahmat; Ainul Yaqin Salam (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Self-awareness is a state of awareness in evaluating oneself so that one is able to control oneself. Personal Hygiene ability is an effort to maintain cleanliness and prevent disease to improve health status. This study aims to determine whether there is an effect of peer group education on self-awareness and personal hygiene ability during menstruation. One group Pre-post design with questionnaires makes up the research methodology. . Saturated sampling, with inclusion and exclusion criteria, utilized to collect data from 42 respondents from all pupils. The results of this study obtained self-awareness and personal hygiene ability at the time of pre-post. The pretest self Awareness result fot the majority of the less category, which included 36 respondents (83.3%). The majority of the medium category in the post test data consisted of 29 respondent (69.0%). Meanwhile, the majority of personal hygiene ability in the pretest category was sufficient as many as 28 respondents (66.7%). The majority of post-test data were in sufficient category as many as 34 respondents (81.0%). Wilcoxon test results obtained p-value : 0.000 and it can be concluded that there is Effect of Peer Group Education on Self Awareness and Personal Hygiene ability during Menstruation on Adoloscent at The Sabilul Hasan Islamic Boarding School Probolinggo.